Trauma, attachment style, and somatization: a study of women with dyspareunia and women survivors of sexual abuse - Michal Granot; Yoram Yovell; Eli Somer; Ahuva Beny; Ronit Sadger; Ronit Uliel-Mirkin; Yaara Zisman-Ilani (BMC, 2018)
Abstract Background Evidence points toward shared characteristics between female survivors of sexual abuse and women with dyspareunia. This study explored, for the first time, similarities and differences between women who were exposed to sexual abuse to those with dyspareunia, in order to examine whether insecure attachment styles and high somatization level are associated with trauma among women with dyspareunia. Methods Attachment styles were explored using the Experience in Close Relationships Scale to reflect participants' levels of anxiety and avoidance. Somatization was assessed using the Brief Symptom Inventory focusing on the frequency of painful and non-painful bodily complaints. Trauma was categorized into three levels: sexual trauma, nonsexual trauma, and no trauma. Results Sexually abused (SA) women (n = 21) compared to women with dyspareunia (dys) (n = 44) exhibited insecure attachment styles, as expressed by high levels of avoidance (SA 4.10 ± 0.99 vs. dys 3.08 ± 1.04, t (61) = 2.66, p = .01) and anxiety (SA 4.29 ± 1.22 vs. dys 3.49 ± 1.04, t (61) = 3.61, p = .001), and higher somatization (21.00 ± 8.25 vs. 13.07 ± 7.57, t (59) = 3.63, p = .001). Attachment and somatization level did not differ significantly between women with dyspareunia without trauma to those with nonsexual trauma. Conclusions Our findings emphasized the unique role of sexual trauma as a contributing factor to the augmentation of perceived bodily symptoms and to insecure attachment style. This illuminates the importance of disclosing previous sexual abuse history among women with dyspareunia.